Edwin H. Sutherland: an improbable criminological key thinker - for critical criminologists and for mainstream criminologists - Friedrichs, David O. (Critical criminology, 2017)
Edwin H. Sutherland’s status as a key thinker among criminologists - for many critical criminologists as well as mainstream criminologists - is addressed, with special attention to the various dimensions of his background that render this status highly improbable. Sutherland’s principal contributions to criminology are identified along with the limitations of these contributions. While Sutherland is especially known for his theory of differential association, his own history suggests that "influence" broadly conceived is complex and idiosyncratic and does not lend itself well to straightforward prediction, hence a "theory" of differential influence (applying differential quite differently from Sutherland) is advanced. Some attention is devoted to contemporaries or near contemporaries (including the Dutch Marxist Willem Bonger) of Sutherland in relation to why their influence has been more limited than that of Sutherland. Criminological "influence" is complex, and not easily testable. A closing section identifies some typically overlooked radical observations of Sutherland’s.